Cancer incidence in the vicinity of open landfills in Guadeloupe, French West Indies - Bernard Bhakkan-Mambir; Danièle Luce; Jacqueline Deloumeaux (BMC Public Health)
Abstract Background People living in the vicinity of a landfill may be exposed to a wide range of pollutants, with possible subsequent health effects, including increased risks of cancer. The aim of the present study was to explore associations between cancer incidence and proximity to the main open landfills in Guadeloupe. Methods We used data from the Guadeloupe cancer registry over the period from 2008 to 2017. We conducted analyses for the 18 most frequent cancer sites. We used the Besag York and Mollié model to study the association between cancer incidence and distance from a landfill, with adjustment for social deprivation. Results People who lived less than 2 km from a landfill had increased risks of ovarian and head and neck cancer. Elevated risks of pancreatic cancer, prostate cancer, lung cancer and melanoma in men, as well colon cancer and hormone receptor-negative breast cancer in women, were also observed. Conclusion A link between exposure to pollutants generated by a landfill and the risk of developing certain cancers was suggested but should be confirmed by additional studies involving a better characterization of exposure and control of potential confounders.